Morphology of Palatal Rugae in Various Sagittal Skeletal Malocclusions in Kerala Population- A Retrospective Study (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present study was designed evaluate the structural morphology of palatal rugae in Kerala orthodonticsubjects with varying Sagittal Skeletal Malocclusions. Pretreatment maxillary casts of 105 patients wereanalyzed for rugae patterns qualitatively and quantitatively using modified Thomas and Kotze classification.The data were statistically analyzed. According to the Fishers exact test, the most common type of rugaepattern in all the groups (Class I, Class II, and Class III) were observed to be wavy followed by curved.Skeletal Class III had the highest number of straight rugae 71.4% among the three groups which wasstatistically significant. Direction of rugal alignment was horizontal and droplet-shaped incisive papillawas identified among different skeletal dysplasia groups.Palatal ruage may serve as valuable indicators forpopulation identification and help in facial reconstructions through their association with varying skeletalmalocclusions.
Keywords: Palatal Rugae Pattern, Skeletal Malocclusion, Dental Casts, Forensic Dentistry